2017
DOI: 10.1007/s00240-017-0997-7
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous paracetamol vs ibuprofen in renal colic: a randomised, double-blind, controlled clinical trial

Abstract: Pain management is one of the essentials of emergency care. Renal colic secondary to urinary stone disease forms one of the most intense pain types. The present study aimed to compare the effect of intravenous ibuprofen to paracetamol in ceasing renal colic. This randomised double-blind study was composed of two intervention arms, intravenous paracetamol and intravenous ibuprofen. Study subjects were randomised to receive a single dose of either paracetamol, 1 g in 100 ml normal saline, or ibuprofen (800 mg in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…More rapid effect of ibuprofen compared with paracetamol has also been confirmed in Cenker et al study (15). Imani et al have also suggested that combining a lower than usual dose of ketorolac with dexmedetomidine can also be effective in post-caesarean pain management (17).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…More rapid effect of ibuprofen compared with paracetamol has also been confirmed in Cenker et al study (15). Imani et al have also suggested that combining a lower than usual dose of ketorolac with dexmedetomidine can also be effective in post-caesarean pain management (17).…”
Section: Discussionsupporting
confidence: 59%
“…The sample size was estimated as 50 people in each group considering the decrease of 3 points on VAS as clinically significant, standard deviation of ketorolac and ibuprofen effectiveness in reducing migraine pain on VAS were 2.88 and 1.44 (15, 16), α = 0.05, and β = 0.1. The data were analyzed using SPSS version 21.…”
Section: Methodsmentioning
confidence: 99%
“…[ 12 ] Besides, some previous research has made comparative evaluation of these two drugs, especially in the treatment of pain. [ 13 14 ] In this regard, our study is a first in the literature comparing the effectiveness of IV paracetamol and ibuprofen on fever management in adult patients in ED. It should also be noted that the two patient groups in our study did not differ in sociodemographic data and clinical scores as well as in laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…24 IV ibuprofen (800 mg) is more effective than IV paracetamol (1 g) in reducing renal colic pain. 25 To the best of our knowledge, a study that compared analgesic effects of IV ibuprofen and paracetamol in repeated doses after laparoscopic cholecystectomy has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%